Pembelajaran PPR Untuk Meningkatkan Literasi Numerasi Pada Konsep Bilangan Mahasiswa - Andri Anugrahana; Cintya Hasthiolivia (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
This study aims to determine whether PPR learning can improve numeracy literacy in the concept of numbers in students. This type of research was descriptive qualitative research with a sample of 24 Elementary School Teacher Study Program students. Pretest and posttest are used to find out whether there is an increase in student knowledge, and observation is used to find out the implementation of lectures with PPR dynamics. The results of this study indicate that: (1) students attend lectures with PPR dynamics; (2) numeracy literacy in the number concept of students. The results of the study showed that there was an increase in numeracy literacy in the number concept of students by 28%.